2008
DOI: 10.1149/1.2899021
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Investigation of 49-Cell Combinatorial Library of Titanium-Based Alloys Fabricated by DMD

Abstract: This combinatorial materials science study investigated the corrosion resistance of titanium alloys. A combinatorial library of 49 alloys of titanium was fabricated by the direct metal deposition ͑DMD͒ technique. This library consisted of a single cube of metal with discrete 4 ϫ 4 ϫ 20 mm regions, each region containing discrete, selected percentages of aluminum and iron. In situ characterization of these regions allowed a rapid evaluation of the 49 alloys for potential use in biomedical implants. The resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the limited work available, Cai et al18 found that increasing Cr increased the corrosion resistance of a clad Cr alloyed Ni 2 Si/NiSi nickel silicide coating. Pimenova and Starr19 tested 49 different laser deposited Ti– x Al– y Fe alloys, concluding that the uneven distribution of alloying elements in the phases resulted in generally poor corrosion resistance in biofluids. However, this work took no account of possible dilution effects when depositing a protective layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the limited work available, Cai et al18 found that increasing Cr increased the corrosion resistance of a clad Cr alloyed Ni 2 Si/NiSi nickel silicide coating. Pimenova and Starr19 tested 49 different laser deposited Ti– x Al– y Fe alloys, concluding that the uneven distribution of alloying elements in the phases resulted in generally poor corrosion resistance in biofluids. However, this work took no account of possible dilution effects when depositing a protective layer.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput characterization techniques have been widely used in corrosion science, such as the development of new corrosion inhibitors 1,2 and coatings, 3,4 corrosion screening of alloys, 5,6 and investigations into the corrosion mechanism of metals, 7 etc. Local electrochemical techniques, as opposed to traditional electrochemical methods, are better suited for high-throughput characterization of the metal corrosion process.…”
mentioning
confidence: 99%